Designing advanced biochar products for maximizing greenhouse gas mitigation potential. Issue 17 (1st September 2016) - Mandal, Sanchita; Sarkar, Binoy; Bolan, Nanthi; Novak, Jeff; Ok, Yong Sik; Van Zwieten, Lukas; Singh, Bhupinder Pal; Kirkham, M. B.; Choppala, Girish; Spokas, Kurt; Naidu, Ravi
ABSTRACT: Greenhouse gas (GHG) emissions from agricultural operations continue to increase. Carbon (C)-enriched char materials like biochar have been described as a mitigation strategy. Utilization of biochar material as a soil amendment has been demonstrated to provide potentially greater soil GHG suppression due to its interactions in the soil system. However, these effects are variable and the duration of the impact remains uncertain. Various (nano)materials can be used to modify chars to obtain surface functionality to mitigate GHG emissions. This review critically focusses on the innovative methodologies for improving char efficiency, underpinning GHG mitigation and C sequestration.